KUALITAS AUDIT, KARAKTERISTIK PERUSAHAAN DAN MANAJEMEN LABA RIIL - Christina Dwi Astuti; Nandha Pangestu (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
This study aims to get the empirical evidence the impact of audit quality and company’s characteristics on real earnings management in manufacturing companies listed at the Indonesia Stock Exchange. Real earnings management in this study is usingRoychowdhury’s model. Overall, real earnings management is measured through abnormal operating cash flow, abnormal production and other abnormal costs, for audit quality using Big Four and Non Big Four audit firm, for company characteristics using company’s size, leverage, and profitability.The population used in this study were all manufacturing companies that met the specified criteria and were listed at the Indonesia Stock Exchange from 2011 to 2018. Total of 18 companies were selected using the purposive sampling method, so it gathered 144 data to process. The analysis technique using the Multiple Regression Analysis.The results of testing the hypothesis in this study indicate that leverage and profitability has positive impact on real earnings management, while audit quality and size does not impact on it. If leverage and profitability are higher, it can be indicated that the company carried out a real earnings management.